2000
DOI: 10.1515/cclm.2000.182
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Therapy with Prostaglandin E1 (Alprostadil) after Orthotopic Liver Transplantation: the Usefulness of Procalcitonin (PCT) and Hepatic Artery Resistive Index (RI) for the Evaluation of Early Graft Function and Clinical Course

Abstract: Increasing demand for donor organs has led to new pharmacological concepts for reducing ischemia-reperfusion injury (I/R) of the graft after liver transplantation to prevent primary non-functioning of the organ. Prostaglandins have proved to be cytoprotective in several experimental models of ischemia and transplantation. The prophylactic administration after orthotopic liver transplantation is still a subject of controversial discussion. The aim of our study was the evaluation of the post-transplant hepatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
11
1
1
Order By: Relevance
“…The mechanism of the transient increase in PCT immediately after LT remains unclear. Some investigators have suggested that PCT synthesis in the graft liver transiently increases just after LT, direct endotoxin influx into the systemic circulation from the small intestine and colon increases during the anhepatic phase, and that transient impairment of endotoxin clearance in the graft liver would be involved . In the present study, serum PCT levels until POD 7 in patients who underwent DDLT were significantly higher than in those who underwent LDLT, although the number of DDLT was small ( n = 14).…”
Section: Discussioncontrasting
confidence: 49%
“…The mechanism of the transient increase in PCT immediately after LT remains unclear. Some investigators have suggested that PCT synthesis in the graft liver transiently increases just after LT, direct endotoxin influx into the systemic circulation from the small intestine and colon increases during the anhepatic phase, and that transient impairment of endotoxin clearance in the graft liver would be involved . In the present study, serum PCT levels until POD 7 in patients who underwent DDLT were significantly higher than in those who underwent LDLT, although the number of DDLT was small ( n = 14).…”
Section: Discussioncontrasting
confidence: 49%
“…Treatment with PGE 1 showed beneficial effects in reducing myocardial or hepatocellular I/R injury in patients during cardiac surgery (27) or after orthotopic liver transplantation (46, 32).…”
Section: Clinical Evidence Of I/r Injury and Treatment Applicationsmentioning
confidence: 99%
“…The aim of this study was to assess preoperative NLR as a prognostic tool of graft function following LDLT. Specifically, we investigated whether NLR could predict EAD following LDLT and compared it with other inflammation‐based indices such as C‐reactive protein (CRP), procalcitonin, lymphocyte‐to‐monocyte ratio (LMR), absolute lymphocyte count, platelet‐to‐lymphocyte ratio (PLR) and the Glasgow prognostic score (GPS). We further evaluated the association between NLR and 1‐year graft failure and 1‐year mortality following LDLT and described the dynamic changes of NLR during the perioperative LDLT period.…”
Section: Introductionmentioning
confidence: 99%